Modulation of Fermentation Quality and Metabolome in Co-ensiling of Sesbania cannabina and Sweet Sorghum by Lactic Acid Bacterial Inoculants - Xia, Tianqi; Wang, Tianwei; Sun, Jiahao; Shi, Weixiong; Liu, Yayong; Huang, Fuqing; Zhang, Jiaqi; Zhong, Jin (Frontiers in Microbiology, 2022)
Sesbania cannabina (SC) is a protein-rich roughage that thrives under moderate-severe saline-alkali (MSSA) soils with the potential to relieve the shortage of high nutritive forage. Sweet sorghum (SS) also tolerates MSSA soils and contains rich fermentable carbohydrates which could improve the fermentation quality in mixed silage. The present study investigated the silage quality, bacterial community, and metabolome in the mixed silage of SC and SS (SC-SS) with or without lactic acid bacterial (LAB) inoculants. Four ratios (10:0, 7:3, 5:5, and 3:7) of SC and SS were treated with sterile water or LAB inoculants (homofermentative Companilactobacillus farciminis and Lactiplantibacillus plantarum, and heterofermentative Lentilactobacillus buchneri and Lentilactobacillus hilgardii), which were analyzed after 60 days of ensiling. Results revealed that LAB inoculation improved the fermentation quality by increasing the lactic acid content and decreasing the ammonia nitrogen and butyric acid contents compared with the untreated group. LAB inoculation also raised the relative feed value by reducing indigestible fibers [e.g., neutral detergent fiber (NDF), acid detergent fiber, and hemicellulose]. Microbial and metabolomic analysis indicated that LAB inoculants could modify the bacterial community and metabolome of SC-SS silage. In co-ensiling samples except for SC alone silage, L. buchneri and L. hilgardii were the dominant species. Metabolites with bioactivities like anti-inflammatory, antioxidant, antimicrobial, and anti-tumor were upregulated with LAB inoculation. Furthermore, correlation analysis demonstrated that active metabolites (e.g., glycitin, glabrene, alnustone, etc.) were positively correlated with L. buchneri, while tripeptides (e.g., SPK, LLK, LPH, etc.) were positively correlated with L. hilgardii. Adequately describing the SC-SS silage by multi-omics approach might deepen our understanding of complicated biological processes underlying feature silages fermentation. Moreover, it may also contribute to screening of targeted functional strains for MSSA-tolerating forage to improve silage quality and promote livestock production.